The War of the Worlds - Wells, H.G (University Press Plc, 2007)
This book is a novel that depicts an alien invasion of the Earth, accompanied by mass destruction and violence. Ray Ferrier, is an ordinary dock worker living in New Jersy. His life is not in order. His small town life is shaken violently by the arrival of destructive intruders. Estranged from his family he has to protect his children against the alien invaders. But how did he protects and provide a secured shelter for his children?...
Keywords: Juvenile Fiction